The Role of Parents in Uplifting Girl-Child Education in Karambi Sub- County Kasese District. - Ndungo, Erisa (Kabale University, 2024)
This study examined the role of Parents in Uplifting girl-child Education in Karambi Sub County Kasese District. The study was guided by the following specific objectives: to determine the problems faced by the girl child education in Karambi sub-county Kasese district, to find out the effects of the problems on the girl child education in Karambi sub-county Kasese district, and to determine the solutions to the problem of the girl child education in Karambi sub-county Kasese district. A descriptive survey design was used for the research study. The target population was 280 people from which a sample of 165 respondents was selected using purposive sampling. Questionnaires and interview guides were the selected tools for data collection. Editing of the questionnaires was done to ensure there were no errors. A qualitative method of analysis was used. Analysis of quantitative data was done using statistical analysis techniques such as frequencies, means, and percentages. Analysis of qualitative data was done using content analysis. The presentation of the data was done using tables. The study findings revealed that the biggest problem hindering girls' education is forced early marriage and that drop out of girl child students affects the standards and performance of other students. The most appropriate solution to the problem of girl child education is ensuring inclusive and equitable quality education for all. The study recommended that a girl child acquire basic. education as this is their outmost right stipulated in the constitution of Uganda.